Equilibrium Thermodynamics, Formation, and Dissociation Kinetics of Trivalent Iron and Gallium Complexes of Triazacyclononane-Triphosphinate (TRAP) Chelators: Unraveling the Foundations of Highly Selective Ga-68 Labeling - Vágner, Adrienn; Forgács, Attila; Brücher, Ernő; Tóth, Imre; Maiocchi, Alessandro; Wurzer, Alexander; Wester, Hans-Jürgen; Notni, Johannes; Baranyai, Zsolt (Frontiers in Chemistry, 2018)
In order to rationalize the influence of FeIII contamination on labelling with the 68Ga eluted from 68Ge/68Ga-generator, a detailed investigation was carried out on the equilibrium properties, formation and dissociation kinetics of GaIII- and FeIII-complexes of 1,4,7-triazacyclononane-1,4,7-tris(methylene[2-carboxyethylphosphinic acid]) (H6TRAP). The stability and protonation constants of the [Fe(TRAP)]3- complex were determined by pH-potentiometry and spectrophotometry by following the competition reaction between the TRAP6- ligand and benzhydroxamic acid (0.15 M NaNO3, 25 C). The formation rates of [Fe(TRAP)]3- and [Ga(TRAP)]3- complexes were determined by spectrophotometry and 31P-NMR spectroscopy in the pH range 4.5–6.5 in the presence of 5–40 fold HxTRAP(x-6) excess (x = 1 and 2, 0.15 M NaNO3, 25 C). The kinetic inertness of [Fe(TRAP)]3- and [Ga(TRAP)]3- was examined by the trans-chelation reactions with 10 to 20-fold excess of HxHBED(x-4) ligand by spectrophotometry at 25 C in 0.15 M NaCl (x=0,1 and 2). The stability constant of [Fe(TRAP)]3- (logKFeL = 26.7) is very similar to that of [Ga(TRAP)]3- (logKGaL = 26.2). The rates of ligand exchange reaction of [Fe(TRAP)]3- and [Ga(TRAP)]3- with HBED are similar. The reactions take place quite slowly via spontaneous dissociation of [M(TRAP)]3-, [M(TRAP)OH]4- and [M(TRAP)(OH)2]5- species. Dissociation half-lives (t1/2) of [Fe(TRAP)]3- and [Ga(TRAP)]3- complexes are 1.1x105 and 1.4x105 h at pH = 7.4 and 25 C. The formation reactions of [Fe(TRAP)]3- and [Ga(TRAP)]3- are also slow due to the formation of the unusually stable monoprotonated [*M(HTRAP)]2- intermediates (*logKGa(HL) = 10.4 and *logKFe(HL) = 9.9), which are much more stable than the [*Ga(HNOTA)]2- intermediate (*logKGa(HL) = 4.2)). Deprotonation and transformation of the monoprotonated [*M(HTRAP)]2- intermediates into the final complex occur via OH–-assisted reactions. Rate constants (kOH) characterizing the OH–-driven deprotonation and transformation of [*Ga(HTRAP)]2- and [*Fe(HTRAP)]2- intermediates are 1.4x105 M–1s–1 and 3.4x104 M–1s–1, respectively. In conclusion, the equilibrium and kinetic properties of [Fe(TRAP)]3- and [Ga(TRAP)]3- complexes are remarkably similar due to the close physico-chemical properties of FeIII and GaIII-ions. However, a slightly faster formation of [Ga(TRAP)]3- over [Fe(TRAP)]3- provides a rationale for a previously observed, selective complexation of 68GaIII in presence of excess FeIII.